Using next generation electronic medical records for laboratory quality monitoring - Loh, Tze Ping; Badrick, Tony (Journal of Laboratory and Precision Medicine, 2017)
The increasing commoditization of laboratory practice risked favouring speed and cost at the expense of quality. Recent retroactive reagent recalls and literature reports of failure to detect significant analytical deviation suggest that the practice of traditional quality control measures is increasingly insufficient to maintain the quality required for resource restricted, high throughput and complex laboratory testing environment. Newer, patient result-based quality techniques have shown good capability in detecting analytical errors. However, a limitation of such techniques is the difficulty in determining whether a breach in control limit is due to an analytical error or a shift in underlying population being monitored. The next generation electronic medical record is an information technology system that brings together different silos of healthcare databases. It has the potential to significantly alter the way laboratory practices quality control by matching patient result-based laboratory observations with clinical practice and findings. This way, any significantly abnormal laboratory findings can be quickly verified with clinical information. It is possible that the traditional internal quality control practice will be replaced by these techniques, although more research is required before this becomes commonplace.